1983
DOI: 10.1038/jcbfm.1983.25
|View full text |Cite
|
Sign up to set email alerts
|

Recirculation in the Rat Brain following Incomplete Ischemia

Abstract: Summary: The objective of this study was to charac terize local cerebral blood flow (CBF) in the recirculation period following incomplete forebrain ischemia. Specifi cally, we wished to determine whether perfusion defects developed in the immediate recirculation period, to study how initial hyperemia and delayed hypoperfusion at the local level were related to the severity of the preceding ischemia, and to find out whether reflow was influenced by the nutritional state of the animals. To that end, fore brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(36 citation statements)
references
References 17 publications
6
30
0
Order By: Relevance
“…These results are consistent with the previous literature (6,7,(15)(16)(17)(18), in which many investigators have failed to find the correlation between the degree of hypoperfusion and the degree of metabolic or histological changes in several models of transient cerebral ischemia. It has also been suggested that the post-ischemic hypoperfusion may occur secondarily to the primary cellular damage by ischemia itself (14,18,19).…”
Section: Resultssupporting
confidence: 83%
“…These results are consistent with the previous literature (6,7,(15)(16)(17)(18), in which many investigators have failed to find the correlation between the degree of hypoperfusion and the degree of metabolic or histological changes in several models of transient cerebral ischemia. It has also been suggested that the post-ischemic hypoperfusion may occur secondarily to the primary cellular damage by ischemia itself (14,18,19).…”
Section: Resultssupporting
confidence: 83%
“…Cerebral blood flow measured in the cortex was found to be less than 10% of the preischemic level after 10 to 15 mins of incomplete ischemia (Kagstrom et al, 1983;Inamura et al, 1988;Dirnagl et al, 1993), which is in agreement with our observations. After 5 mins reperfusion, a 250% to 300% hyperemia was usually seen (Kagstrom et al, 1983;Dirnagl et al, 1993), which is lower than the peak value observed 9 to 10 mins after the end of the ischemia in our study (538%±35%). These differences might be related to differences in anesthesia or duration of ischemia between the studies.…”
Section: Discussionsupporting
confidence: 82%
“…The phenomenon of hypoperfusion and postischemic hyperperfusion has been investigated extensively after severe incomplete ischemia in rat (Kagstrom et al, 1983;Inamura et al, 1988;Dirnagl et al, 1993). Cerebral blood flow measured in the cortex was found to be less than 10% of the preischemic level after 10 to 15 mins of incomplete ischemia (Kagstrom et al, 1983;Inamura et al, 1988;Dirnagl et al, 1993), which is in agreement with our observations.…”
Section: Discussionsupporting
confidence: 82%
“…Recent results have associated increased expression of uncoupling protein-2 (UCP-2) with neuroprotection (Diano et al, 2003;Mattiasson et al, 2003), but its potential impact on ischemic depolarization per se is unclear. Established global ischemia models are characterized by very low residual flow during occlusion (Kågströ m et al, 1983;Pulsinelli et al, 1982), but perfusion effects of preconditioning are also possible. Better preservation of CBF and ATP levels during global ischemia has been shown in rat cortex after several days of ipsilateral carotid artery occlusion (Bronner et al, 1998).…”
Section: Changes In Depolarization Kinetics Associated With Preconditmentioning
confidence: 99%